Introduction to the special section: Agrarian transformation in Thailand - Commodities, landscapes, and livelihoods - Sukanlaya Choenkwan; Micah R. Fisher (Forest and Society, 2018)
This is an introduction and review for a special section on agrarian transformation in Thailand. The article seeks to guide greater attention toward issues affecting rural Thai landscapes and livelihoods. Through the examination of specific commodities across various geographies, the paper seeks to refocus research towards decision making processes among rural communities. The research draws on field study cases that follow various aspects of particular commodities, including rubber, pomelo, tomato, cassava, and furthermore, incorporates complementary research in Forest and Society on coffee, ginger, jujube, and agrotourism in Thailand. Through the factors shaping engagement with these agricultural commodities, we examine issues including labor, soil fertility, contract farming arrangements, drought resistant crops, climate change, and others. In this way we seek to draw attention to the complex dynamics taking place on the Thai rural landscape and the factors that are reshaping land relations. Through initiating a research network on similar research approaches we identify and envision broader opportunities for helping to re-imagine future possibility in rural Thailand.